2021
DOI: 10.1155/2021/2545151
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Human Skeleton Detection and Extraction in Dance Video Based on PSO‐Enabled LSTM Neural Network

Abstract: With the significant increase of social informatization, the emerging information technology represented by machine vision has been applied to more and more scenes. Among them, the detection and extraction of human skeleton in a dance video based on this technology has a huge market demand in education and training. However, the existing detection and extraction technology has the problems of slow recognition speed and low extraction accuracy. Therefore, this paper proposes a neural network based on particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The skeleton data is extracted from input video using the skeleton extraction technique [22], which involves capturing frames with various human joint coordinates. This data is used to evaluate a specific human's skeleton, as it contains positional data on The DDSTGCNN uses skeleton data to create higher-level feature mappings and joint positional trajectory on graph nodes.…”
Section: Skeleton Data Processing By Dynamic Dense Spatio-temporal Gr...mentioning
confidence: 99%
“…The skeleton data is extracted from input video using the skeleton extraction technique [22], which involves capturing frames with various human joint coordinates. This data is used to evaluate a specific human's skeleton, as it contains positional data on The DDSTGCNN uses skeleton data to create higher-level feature mappings and joint positional trajectory on graph nodes.…”
Section: Skeleton Data Processing By Dynamic Dense Spatio-temporal Gr...mentioning
confidence: 99%
“…The global optimal position gbest and local optimal position pbest are determined by the initial Fitness value of the particles [ 33 ], and they are regarded as the historical optimal positions. According to the speed and position of the updated particles, the corresponding particle Fitness value is calculated and then updated to improve the prediction accuracy.…”
Section: Collision Risk Prediction Modelmentioning
confidence: 99%
“…The termination condition is judged to be satisfied (the Fitness value of particles tends to be stable or reaches the maximum number of iterations with iteration [ 33 ]). If the termination condition is satisfied, optimal parameters are assigned to PSO-LSTM model; otherwise, step (4) is returned.…”
Section: Collision Risk Prediction Modelmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%